Strangers at home: narratives of northern Muslim returnees in post-war Sri Lanka - Chattoraj, Diotima; Gerharz, Eva (National Science Foundation: Colombo, 2019)
This article focuses on the experiences, aspirations and challenges of Sri Lankan Muslim returnees to northern part of Sri Lanka in Jaffna and analyses their strategies to cope with the ambivalent situation thereafter. The empirical point of departure is drawn from the stories of three Muslim returnees in Jaffna who returned from different parts of Sri Lanka. The article finds that the Muslim returnees conceptualise home as a place where they can have a “better future” than the displaced location where they stayed for so long. The authors argue that this unveils the different kinds of attachment they have to their homes through memories, emotions and material and immaterial properties. There exists feelings of alienation and detachment from their homes among some. Furthermore, their aspirations of a good life seem to be decaying in their homes after their return.
Keywords: Home; Return; Muslim returnees; Attachment; Belonging